What everyone should know about homosexuality - LaHaye, Tim F. (Wheaton, IL Tyndale, 1978)
Includes bibliographical references.
Donated by Pieter Dijkstal, 5/2003
Keywords: Homosexuality -- religious aspects -- Christianity